Role of Digital Literacy: Information Processing Of Skincare On Twitter Beauty Bases - Yoland Apresia Brillian; Miftahul Rozaq (Eduvest - Journal of Universal Studies, 2025)
Information about skincare on the beauty base account on Twitter is not necessarily accurate, there are many promotional elements carried out by buzzers and also affiliates. In accessing information about skincare, of course, it is necessary to be careful so that the chosen skincare product can work effectively and so as not to be negatively affected. So how is the information processing on beauty base users on Twitter who have experienced mistakes in purchasing skincare products due to a lack of digital literacy? This study aims to examine how to process skincare information on the Twitter beauty base on users who have experienced mistakes in purchasing skincare products. The method used is a qualitative method and the data is processed using Nvivo 12 software. The results of the study show that users are aware of promotions on beauty base accounts on Twitter, but the user's memory is limited, so users need external help to remember information about skincare that has been accessed through the beauty base on Twitter.